PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN (STUDI KASUS DI KAMPAR BAKERY BANGKINANG) - Rahmad Akbar; Andri Nofiar Am (Jurnal Manajemen, 2021)
This study aims to determine and explain about the effect of service quality and brand image on customer loyalty mediated by customer satisfaction on Kampar Bakery Bangkinang bread products. The data analysis using path analysis (Path Analysis). This study uses quantitative data. Random data collection techniques. Data sources in this study were from Kampar Bakery Bangkinang from 2013 until 2018. The data analysis techniques were descriptive analysis, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. The results of this study are as follows 1) Service quality has a positive and significant influence on customer satisfaction Kampar Bread Products Bakery. 2) Brand image has a positive and significant influence on customer satisfaction Kampar Bread Products Bakery. 3) Service quality has a positive and significant influence on customer loyalty Kampar Bread Products Bakery. 4) Brand image has a positive and significant influence on customer loyalty Kampar Bread Products Bakery. 5) Customer satisfaction has a positive and significant influence on customer loyalty Kampar Bread Products Bakery. 6) Service quality has a positive and significant influence on customer loyalty through customer satisfaction Kampar Bread Products Bakery. 7) Brand image has a positive and significant influence on customer loyalty through customer satisfaction Kampar Bread Products Bakery.